Determinação multiclasse de resíduos de antimicrobianos em músculo de frango empregando limpeza por SPE e UHPLC-MS/MS - Floriano, Luana (2022)
Antimicrobials have been widely used in the prevention and/or treatment of diseases within the broiler supply chain in order to maintain productivity. The indiscriminate use of these veterinary drugs can, however, lead to the presence of residues in the edible tissues of the treated animal, and thus pose risks to the consumer’s health. Therefore, the development of analytical methods that allow the monitoring of these residues is very importance to ensure food safety. In this work, a method was developed and validated for the multiclass determination of 31 antimicrobial residues in chicken muscle by ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). All sorbents tested during sample preparation were evaluated in terms of efficiency in reducing phospholipids present in the matrix extract. The extraction step was carried out using 2 g of sample, 2 mL of ultrapure water (stirring) and 8 mL of acetonitrile acidified with 1% (m/v) oxalic acid, followed by stirring and centrifugation. Afterwards, a cleaning step was performed using solid-phase extraction (SPE) in the pass-through mode, in which 3 mL of supernatant was eluted directly through the Bond Elut C18 cartridge (500 mg). For substances with a maximum residue limit (MRL) ≥ 100 μg kg-1, the extract was diluted 5 times in ultrapure water. For substances without a defined MRL and for trimethoprim, 1 mL of the extract was evaporated to dryness (N2; 45 ºC) and reconstituted in 1 mL of water:acetonitrile (80:20, v/v). The validation parameters evaluated were selectivity, matrix effect, linearity, trueness (by recovery), precision and decision limit. The procedures were performed using fortified blank matrix analysis to compensate for the matrix effects obtained (between -20% and +152%). All compounds showed linearity in the working ranges evaluated, either from 0 to 2.0 times the MRL for permitted substances or from 0 to 4.0 times the lowest calibrated level (LCL) for unauthorized substances, with coefficients of determination greater than 0.97. The trueness, assessed at levels 0.5; 1.0 and 1.5 times the LMR; and 1.0; 2.0 and 3.0 times the LCL, proved to be adequate, with recoveries between 90 and 117%. The method was applied to 24 chicken muscle samples from different Brazilian states. Only oxytetracycline was detected in one sample, but below the lowest concentration level of the analytical curve (25 μg kg-1).